المصلحة الفضلى للطفل في التشريع الجزائري (Revue El-Wahat pour les Recherches et les Etudes, 2023)
ملخص:      تعتبر اتفاقية حقوق الطفل التي اعتمدتها الأمم المتحدة سنة 1989، أول نص قانوني كرّس مبدأ المصلحة الفضلى للطفل، ثم تبنته بعد ذلك الكثير من النصوص الدولية والوطنية، بما فيها التشريع الجزائري، لكن هذه النصوص لم تحدد لنا مفهوما دقيقا لهذا المبدأ. ومن هنا تظهر أهمية هذا الموضوع حيث يرتبط بمصلحة الطفل عند اتخاذ قرارات تخصه سواء من طرف أجهزة الدولة أو السلطات القضائية فيها.تهدف هذه الدراسة إلى الوصول إلى مفهوم للمصلحة الفضلى للطفل ووضع معايير يستعين بها القاضي عند الفصل في أي نزاع تكون فيه مصلحة الطفل معرضة للخطر، ومعرفة إلى أي مدى كرّس المشرع الجزائري المصلحة الفضلى للطفل؟.كلمات دالة: المصلحة الفضلى، الطفل، اتفاقية حقوق الطفل، قانون حماية الطفل، مصلحة المحضون.       Abstract: The Convention on the Rights of the Child, adopted by the United Nations in 1989, is the first legal text that enshrined the principle of the best interest of the child. It was subsequently adopted by many international and national texts, including Algerian legislation, but these texts did not define an accurate understanding of this principle. Hence, the importance of this issue appears in its link to the benefit of the child when making decisions concerning him, whether by state organs or the judicial authorities therein.This study aims to arrive to a concept of the best interest of the child and to establish criteria for the judge to use when adjudicating any dispute in which the interest of the child is at risk, and to find out to what extent did the Algerian legislator enshrine the the best interest of the child?Key words:the best interest, the child, the Convention on the Rights of the Child, the Child Protection Law, the interest of the fostered child.